Sustainable Practices in Culinary Programs: Views of Chef Lecturers Regarding Food Waste Management - Yildirim, Kutay Arda; Yılmaz, Yenilmez Ufuk; Rezapouraghdam, Hamed (My University, 2024)
This study investigates the extent to which corporate social responsibility (CSR) and more specifically, food waste management is incorporated into a university's tourism faculty's practical courses, with a focus on sustainability methods used in food production procedures. The study looks into the crucial issue of food waste, an essential part of sustainable practices, by drawing on the concepts established in the Sustainable Development Goal 12 of the United Nations; Ensuring sustainable consumption and production patterns. The research reveals various viewpoints on CSR and food waste implementation through qualitative research including 11 instructors. The results show a variety of techniques for reducing food waste in practical classes, from careful control to acknowledged flaws in waste management. Notably, the study draws attention to the lack of a specific CSR curriculum for students enrolled in culinary education practical training. In order to provide a more comprehensive knowledge of CSR integration in culinary schools, the paper finishes by outlining possible directions for future research.
Keywords: Sustainability; Food waste; Social responsibility; Culinary programs